Nilai Sun Protection Factor (SPF) dan Antioksidan Ekstrak Bunga Mawar Merah (Rosa damascena Mill.) Sebagai Potensi Tabir Surya - Diyan Sakti Purwanto; Dewi Weni Sari; Vivin Nurkharimah (Jurnal Farmasi Indonesia, 2026)
Excessive exposure to ultraviolet (UV) rays can cause various skin disorders, such as premature aging to skin cancer. Sunscreen made from natural ingredients is an effective solution to protect the skin from UV rays. Red rose flower has the potential as a UV protector and antioxidant. This study aims to determine the SPF value and antioxidant activity of red rose flower extract. This research uses descriptive quantitative method. Samples used red rose flowers with the extraction method, namely maceration using 96% ethanol solvent with a ratio of 1: 5 (b/v) for 3x24 hours. SPF and antioxidant values were determined by UV-Vis spectrophotometric method, with ascorbic acid comparison solution for antioxidant test. The result of the SPF measurement is 34.61538 which is included in the ultra protection type (>15) while the antioxidant rose flower extract obtained IC₅₀ value of 15.09 ppm and vitamin C as a comparison obtained a result of 9.59 ppm, both of which are included in the very strong antioxidant category (IC₅₀ <50 ppm). Thus, red rose flower extract has activity as a sunscreen and a source of natural antioxidants.